Inovasi Sains dalam Organisasi Kepemudaan: Membangun Kesadaran Sosial untuk Pembangunan Berkelanjutan - Riky Pratama Susilo; Al Rafni; Junaidi Indrawadi; Susi Fitria Dewi (Postgraduate, University of Mataram, 2025)
This study aims to analyze the role of youth organizations in increasing youth social awareness in Sei Kandis Village and identify science innovations applied to support sustainable development. The method used is qualitative with a phenomenological approach. Data were collected through observation, interviews, and documentation, with informants determined by purposive sampling. The results showed that Karang Taruna plays an important role in increasing social awareness through science innovation-based programs, such as environmentally friendly technology training. Factors that influence youth social awareness include internal factors, such as enthusiasm and commitment, and external factors, such as adequate facilities and infrastructure. The conclusion of this study is that the application of science innovation in karang taruna programs can increase youth participation in social activities and support sustainable development in the village.